Religious Commodification in Branding: A Semiotic Analysis of Instaperfect’s Instagram Content - Tridifa, Meira (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
The commodification of religion in branding practices has become a prominent phenomenon in contemporary consumer culture, particularly in how religious symbols promote commercial products. Brands have increasingly adopted religious imagery and values to appeal to specific market segments, especially in Muslim-majority regions. This study examines how Instaperfect, a beauty brand, commodifies Islamic elements in its branding on Instagram, focusing on integrating of religious symbols with commercial ideals. The research employs a descriptive qualitative method with a content analysis approach, using John Fiske’s semiotic framework to analyze eight Instagram posts from Instaperfect, published between January and April 2023. Data was collected through a literature review and visual-textual analysis of the selected posts. The results reveal that Instaperfect blends religious symbols with luxury branding to construct an aspirational identity for Muslim women, thereby commodifying religious values. The study highlights how Islamic values such as halal and modesty are reframed to align with capitalist ideologies, turning religious devotion into a commercialized identity. These findings emphasize the growing intersection of religion and consumerism in digital branding. Komodifikasi agama dalam branding semakin banyak ditemui dalam budaya konsumerisme saat ini, terutama dengan penggunaan simbol-simbol agama untuk menarik perhatian konsumen. Banyak merek yang kini memanfaatkan citra agama untuk menjangkau pasar tertentu, khususnya di negara-negara dengan mayoritas Muslim. Penelitian ini bertujuan untuk mengungkap bagaimana Instaperfect, sebuah merek kosmetik, mengkomodifikasi elemen-elemen Islam dalam strategi branding mereka di Instagram, dengan fokus pada cara mereka menggabungkan simbol-simbol agama dengan nilai komersial. Penelitian ini menggunakan metode kualitatif deskriptif dengan analisis konten, serta kerangka semiotika John Fiske untuk menganalisis delapan unggahan Instagram Instaperfect yang dipublikasikan antara Januari hingga April 2023. Data dikumpulkan melalui studi literatur dan analisis visual-teks dari unggahan yang terpilih. Hasil penelitian menunjukkan bahwa Instaperfect memadukan simbol agama dengan branding mewah untuk membangun citra aspiratif bagi perempuan Muslim, yang pada gilirannya mengkomodifikasi nilai-nilai agama. Penelitian ini juga mengungkap bagaimana nilai-nilai Islam seperti halal dan kesederhanaan diposisikan ulang untuk sejalan dengan ideologi kapitalisme, menjadikan religiusitas sebagai identitas komersial.